Autorretrato de un escritor del Perú del Siglo XX: revelaciones en las cartas de José María Arguedas - Nuñez, Gabriela (2016)
Prepared for delivery at the 2016 Congress of the Latin American Studies Association, New York, New York, May 27 - 30, 2016.